Relationship Between Perceived Flexibility And Learners’ Satisfaction Among Students Studying Islamic Sciences Online - Khan, Lamya Feroz (Educompassion: Jurnal Integrasi Pendidikan Islam dan Global, 2024)
The educational landscape is steadily changing with online education. Flexibility is among many factors pertaining to student’s satisfaction with online studies. Flexibility of time which includes when students can start and end their course, timings of assessments and assignments, pace and frequency of learning and duration of course were examined in this paper and its relation to student satisfaction. Students from three online universities participated in the study (N=28) with results showing a moderate positive correlation (0.672) between the two. Thus, flexibility must be an important factor in delivering online education. Self -regulated learning skills comprise of setting objectives, managing time, utilizing effective learning strategies, organizing the study environment, and seeking assistance. The Online Self-Regulated Learning Questionnaire (OSLQ) was used to assess self-regulated learning and its relationship to students’ satisfaction from the same sample. The results showed no statistical significance (rho= 0.08); hence no inference could be made. However, existing literature on self-regulated learning reveals that it is related to academic achievement. Finally, the paper discusses the use of self-regulatory learning skills and strategies in online learning as a means to achieve Ihsan (excellence). Ihsan can be viewed as a spiritual accountability for students. Ihsan will combat the challenges faced by students such as lack of motivation, procrastination etc. and serve as a strategy for an effective online learning experience. This paper seeks to inform developers of online learning platforms of the importance of incorporation of flexibility into their programs and students to develop self-regulatory learning skills as a means of achieving Ihsan in their online education.